PENGARUH UMUR TUMBUHAN AREN TERHADAP PRODUKSI NIRA DI DESA MURUNG A KECAMATAN BATU BENAWA KABUPATEN HULU SUNGAI TENGAH KALIMANTAN SELATAN - Fatriani Fatriani (Lambung Mangkurat University-Indonesia, 2011)
This study aims to determine the effect of age on the sap of palm plants produced from A Murung Village, Sub Batu Benawa Hulu Sungai Tengah District, South Kalimantan. Based on simple linear regression analysis it can be seen the following equation: Y = 12.6612 - 0.2625999 * age plant. Sap production varies inversely with the mean age of palm plants with increasing age, the more little palm plant sap produced. F hit (15.24)> F tab (9:07) means that age has a significant influence on the production of palm juice either at the level of confidence of 5% or 1% of the above regression equation can be estimated (predicted) by age palm juice production plant . The results of the calculation of the correlation coefficient (r) indicates the closeness of the relationship between age with the production of palm juice, this is indicated by r values of -0.734597 (close to -1), mean age of palm plants have a very close correlation with the production of palm juice, while based on the coefficient of determination (R2) known value is 53.9632%, means the production of palm juice is influenced by the age factor while the remaining 53.96% influenced by other factors. Age factor has a strong relationship with the production of palm wine (the correlation coefficient of -0.734597. Age factor is inversely proportional to the roduction of palm juice, palm sugar The older age of the plants produced less sap, Age 11 years generating plants aren aren at most ( 10.68 liters) while the lowest is 30 years old (2.34 liters), Need palm cultivation in the area within the framework of sustainability brown sugar.Technic tapping sugar production in order to maximize the production of palm juice should really be considered, Ways to maximize production Nira through efforts to extend the period of tapping palm bunches of flowers should also be noted.Keywords :Age plants, production, Nira